1999
DOI: 10.4141/a98-022
|View full text |Cite
|
Sign up to set email alerts
|

Acute heat-stress effects on physiology and fear-related behaviour in red jungle fowl and domestic fowl

Abstract: Zulkifli, I., Dass, R. T. and Che Norma, M. T. 1999. Acute heat-stress effects on physiology and fear-related behaviour in red jungle fowl and domestic fowl. Can. J. Anim. Sci. 79: [165][166][167][168][169][170]. Two experiments were conducted to compare heat tolerance of red jungle fowl (RJF) and commercial broilers (CB) at (i) a common age and (ii) a common body weight. In exp. 1, RJF and CB of a common age (8 wk) were exposed to 36 ± 1°C for 6 h. RJF had smaller increases in heterophil to lymphocyte ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
12
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 37 publications
8
12
2
4
Order By: Relevance
“…On supplementation of 100 mg, 200 mg and 300 mg AA in feed, it was found that the overall mean concentration of glucose showed nonsignificant difference between comfort and heat stressed birds in all the groups. Similar to present investigation, various workers reported blood glucose levels in broilers under different thermal stress conditions (Zulkifli et al, 1999;Aksit et al, 2006;Olanrewaju et al, 2010). In present study, significantly higher levels of plasma glucose were observed in 200 mg AA supplemented birds as compared to heat stressed chickens.…”
Section: Resultssupporting
confidence: 89%
“…On supplementation of 100 mg, 200 mg and 300 mg AA in feed, it was found that the overall mean concentration of glucose showed nonsignificant difference between comfort and heat stressed birds in all the groups. Similar to present investigation, various workers reported blood glucose levels in broilers under different thermal stress conditions (Zulkifli et al, 1999;Aksit et al, 2006;Olanrewaju et al, 2010). In present study, significantly higher levels of plasma glucose were observed in 200 mg AA supplemented birds as compared to heat stressed chickens.…”
Section: Resultssupporting
confidence: 89%
“…There are some reports that heat challenge may elevate corticosterone in broiler chickens (Edens and Siegel, 1975;Zulkifli et al, 1999Zulkifli et al, , 2003Zulkifli et al, , 2009Mahmoud et al, 2004). However, Lin et al (2006) and Han et al (2010) reported that HT did not affect plasma corticosterone concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…또한, 선발 육종에 따른 개량화가 진행된 개체일수록 스트레스 반응도가 높다는 결 과를 제시하고 있는데, 적색야계(Red Jungle Fowl)와 토종계 (village fowl) 및 실용 브로일러를 대상으로 열 스트레스 반 응 정도를 비교 분석한 결과, 혈액 생화학 지표, 혈장 코티 코스테론 농도, 열스트레스 단백질(HSP 70) 등 모든 생리적 스트레스 지표에서 실용 브로일러가 야계 및 토종계에 비해 스트레스에 더욱 민감하게 반응하는 양상을 보였다 (Soleimani et al, 2011). (Albentosa et al, 2003;Fraisse와 Cockrem, 2006;Zimmerman et al, 2006;Uitdehaag et al, 2008Uitdehaag et al, , 2009, 스트레스와 관련 한 생리적 표지 물질의 분석으로서는 혈액 생화학적 지표 (Mashaly et al, 1984;Zulkifli et al, 1999;Thaxton et al, 2006;Turkyilmaz, 2008;Kang et al, 2011;Soleimani et al, 2011), 혈장 코티코스테론 농도 (Mashaly et al, 1984;Korte et al, 2005;de Haas et al, 2013, Fraisse와 Cockrem, 2006Mack et al, 2013), 항산화 요산(antioxidant uric acid) 농도 (Munck et al, 1984;Star et al, 2008a), 혈장 3,5,3'-triiodothyronine 농도 (Yahav et al, 1998;Uni et al, 2001;Star et al, 2008a;Mack et al, 2013) 및 세로토닌(5-HT) 농도 Uitdehaag et al, 2011;de Haas et al, 2013)의 분석 등이 널리 소개되고 있다. 이 밖에도 세포 내 텔로미어 (telomere) 함유율, DNA 손상율 및 열 스트레스 단백질(heat shock protein)의 발현율과 같은 DNA 관련 표지들이 개체의 스트레스 정도를 가늠할 수 있는 새로운 생리 표지이다 (Sohn et al, 2012).…”
Section: 로토닌(Serotonin) 수준은 낮게 나타난다고 보고하였다unclassified
“…따라서 본 연구에서는 닭 품 종별 고밀도 사육구와 대조구 간에 혈액 및 간 조직으로부 터 HSP70, HSP90-α, HSP90-β 및 HMGCR 유전자의 mRNA 발현율을 분석 비교하여 이의 결과를 Table 5와 6에 제시하 (Soleimani et al, 2011). 이밖의 많은 연구에서 닭의 품종 및 계통 간 열 적응력의 유전적 차이가 있음을 보고하였고, 더 불어 야계 및 열대지방의 토종닭들이 브로일러에 비해 월등 히 높은 열 적응력을 가졌다고 하였다 (Yahav et al, 1998;Deeb and Cahaner, 1999;Zulkifli et al, 1999;Sandercock et al, 2006;Cahaner et al, 2008). 일반적으로 선발 육종을 통 해 개량이 진행된 개체의 스트레스 반응 정도가 자연 상태 의 개체들에 비해 상대적으로 높은 것으로 알려지고 있다.…”
Section: 로토닌(Serotonin) 수준은 낮게 나타난다고 보고하였다unclassified